A presença das organizações não-governamentais nas políticas de superação das desigualdades raciais - Silva, Juliana Francine da (2008)
The Non-Profit Organizations has been implied their axle of action since the 90 s, actuating with governmental organs and with the private sector. In this work, I investigate the contributions which were brought by The Non-Profit Organizations of racial thematic in the management of politics of recovery regarded with racial mismatched, invariably accomplished with public and private areas, in São Paulo city. We focalize the aspects of participations instigating the elaboration and execution, and of autonomy. The objective is to understand in the clearly form the work of institutions and the formulation of public politics for the black population, besides that, I introduce a historic about the non-profit organizations in Brazil, the coming up of governmental institutional instancy and pointing out the black population and the beginning of politics of affirmatives actions in Brazil. The obtainment of empiric basis came from interviews in working area with professionals which actuate non-profit organizations of racial thematic